1993
DOI: 10.1080/13583149308628615
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals — as seen by the Scanning Tunnelling and Force Microscopes

Abstract: Liquid crystals have provided an invaluable service for the development of the scanning tunnelling microscope (STM). In return, the STM has done well for liquid crystals. What is meant by this anthropomorphising of scientific techniques and materials? The technique of STM was originally confined to the study of metallic surfaces by the belief that only intrinsically conducting materials could be successfully imaged. Then liquid crystals were imaged with stunning clarity. They served as well-behaved subjects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The differences in the thermal ranges between nematic and SmA phases in these mesogens may be due to the influence of alkyl group length because the increase of the alkyl chain length in the compounds leads to strengthened the intermolecular forces between the molecules. [30][31][32] Therefore, the free movement of molecules is decreased and leads to aggregation of the molecules together with the appearance of SmA phase that considers closer to the crystal phase. The OPM and DSC investigations in this study revealed that the last compound in this series (III k ) has only SmA phase with a range of about 180°C upon heating scan.…”
Section: Mesomorphic Behaviors Of Compounds (Iii A-k )mentioning
confidence: 99%
“…The differences in the thermal ranges between nematic and SmA phases in these mesogens may be due to the influence of alkyl group length because the increase of the alkyl chain length in the compounds leads to strengthened the intermolecular forces between the molecules. [30][31][32] Therefore, the free movement of molecules is decreased and leads to aggregation of the molecules together with the appearance of SmA phase that considers closer to the crystal phase. The OPM and DSC investigations in this study revealed that the last compound in this series (III k ) has only SmA phase with a range of about 180°C upon heating scan.…”
Section: Mesomorphic Behaviors Of Compounds (Iii A-k )mentioning
confidence: 99%
“…interaction (X: halogen atom) [27]. 6CB molecules have head-to-head CN-CN interaction [30,31]. Hence, the small twisting power of the chiral inducer may be because CN-I interaction can break ordered structure of LC matrix.…”
Section: Methodsmentioning
confidence: 99%